Opportunities and Challenges of Halal Chicken Processed Products in Improving the Creative Economy - Dem Vi Sara; Maya Dewi Dyah Maharani (AKSES: Jurnal Ekonomi dan Bisnis, 2022)
The large consumer demand in Indonesia makes the halal food industry in Indonesia.This is also a sign that Indonesia has great potential in this industry. Indonesia can be a major player, not just as a consumer. However, to become a major player Indonesia must be able to face the challenges that exist in the development of the industry. This study aims to identify opportunities and challenges of halal chicken processed products in improving the creative economy in Indonesia. The method in this research is a qualitative method with a type of literature research, namely looking for concept theories that are used as a theoretical basis and information contained in the library in the form of books, articles, papers, and other documents. The results of this study show that halal chicken processed products have an opportunity with high market needs and household consumption of halal food.Keywords: Economy, Food, Halal AbstrakBesarnya permintaan konsumen di Indonesia menjadikan industri makanan halal di Indonesia.Hal ini juga menjadi tanda bahwa Indonesia sangat berpotensi dalam industri ini. Indonesia dapat menjadi pemain utama, bukan hanya sebagai konsumen. Namun, untuk menjadi pemain utama Indonesia harus dapat menghadapi tantangan-tantangan yang ada dalam pengembangan industri tersebut. Penelitian ini bertujuan untuk mengidentifikasi peluang dan tantangan produk olahan ayam halal dalam meningkatkan ekonomi kreatif di Indonesia. Metode dalam penelitian ini adalah metode kualitatif dengan jenis penelitian kepustakaan yaitu mencari teori-teori konsep yang dijadikan landasan teoritis dan informasi yang terdapat di perpustakaan baik berupa buku, artikel, makalah, dan dokumen lainnya. Hasil penelitian ini menunjukkan bahwa produk olahan ayam halal memiliki peluang dengan tingginya kebutuhan pasar dan konsumsi rumah tangga terhadap makanan halal.Katakunci: Ekonomi, Makanan, Halal